2021
DOI: 10.3389/fmars.2021.704721
|View full text |Cite
|
Sign up to set email alerts
|

Copernicus Sea Level Space Observations: A Basis for Assessing Mitigation and Developing Adaptation Strategies to Sea Level Rise

Abstract: It is essential to monitor accurately current sea level changes to better understand and project future sea level rise (SLR). This is the basis to support the design of adaptation strategies to climate change. Altimeter sea level products are operationally produced and distributed by the E.U. Copernicus services dedicated to the marine environment (CMEMS) and climate change (C3S). The present article is a review paper that intends to explain why and to which extent the sea level monitoring indicators derived f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…The products include sea level anomaly sampled at 1 Hz as well as the WTC derived from the MWR on board the altimetry satellites. These along‐track products serve as the basis data for the AVISO+ GMSL data record (Ablain et al., 2019; Guérou et al., 2022) and for the computation of the Copernicus Climate Change Service (C3S) satellite sea level gridded product dedicated to climate change studies (Legeais et al., 2021).…”
Section: Datamentioning
confidence: 99%
“…The products include sea level anomaly sampled at 1 Hz as well as the WTC derived from the MWR on board the altimetry satellites. These along‐track products serve as the basis data for the AVISO+ GMSL data record (Ablain et al., 2019; Guérou et al., 2022) and for the computation of the Copernicus Climate Change Service (C3S) satellite sea level gridded product dedicated to climate change studies (Legeais et al., 2021).…”
Section: Datamentioning
confidence: 99%
“…European Copernicus Services also provide sea level data, with a free and open access policy (Melet et al, 2021). Altimeter sea level products are operationally produced and distributed by the Copernicus Marine Environment Monitoring Service (CMEMS) and by the Copernicus Climate Change Service (C3S) (Legeais et al, 2021), and used to produce Ocean Monitoring Indicators 1 , such as observed mean SLR for the global ocean and regional EU seas, as well as regional sea level trends. In addition, the CMEMS provides tide gauge data, ocean and wave forecasts and reanalyses (Irazoqui Apecechea et al, 2023).…”
Section: The European Perspectivementioning
confidence: 99%
“…Satellite altimeters allow to measure the geocentric sea level, which is the sea level with respect to the centre of mass of the Earth. Since 1993, sea level has been monitored routinely on a daily basis with a resolution of ¼°x ¼° from 82°S to 82°N (e.g., (Legeais et al, 2021). Although sea level dynamics is highly heterogeneous, the time and space samplings are enough to resolve effectively the GMSL dynamics on a weekly basis (Fox-Kemper et al, 2021a;Henry et al, 2014;Scharffenberg and Stammer, 2019).…”
Section: Satellite Recordmentioning
confidence: 99%
“…We compute the GMSL time series from the vDT2021 sea level product operationally generated by the Copernicus Climate Change Service (C3S). This dataset is dedicated to the sea level stability for climate studies (Legeais et al, 2021). It provides daily sea level anomalies grids at a 1/4 degree spatial resolution from January 1993 until August 2021, based at any time on a reference altimeter mission (TOPEX/Poseidon, Jason-1, Jason-2, Jason-3 and Sentinel-6 Michaël Freilich), plus a complementary mission (ERS-1,2, Envisat, Cryosat or SARAL/AltiKa depending on the time frame) to increase the spatial coverage.…”
Section: Altimetry-based Gmtsl Datamentioning
confidence: 99%